Nano formulation development and antibacterial activity of cinnamon bark extract-chitosan composites against Burkholderia Glumae the causative agent of Bacterial Panicle Blight in rice. - Qamar Mohammed-Naji; Dzarifah Zulperi; Khairulmazmi Ahmad; Erneeza Mohd Hata (PLoS ONE)
Bacterial panicle blight (BPB) disease, caused by Burkholderia glumae, poses a significant threat to rice production. Conventional chemical control methods contribute to environmental concerns and resistance issues, necessitating the development of sustainable alternatives. This study aimed to formulate and evaluate cinnamon bark extract-chitosan (CBE- CS) nano formulations for antibacterial efficacy against Burkholderia glumae. First, the antibacterial activity of cinnamon bark extract (CBE) was assessed, revealing a minimum inhibitory concentration (MIC) of 6.25 μg/mL and a minimum bactericidal concentration (MBC) of 12.5 μg/mL. Morphological analysis using scanning electron microscopy (SEM), confocal laser scanning microscopy (CLSM), and transmission electron microscopy (TEM) showed significant bacterial cell wall damage, cytoplasmic leakage, and structural degradation after treatment. Chemical characterization of CBE using gas chromatography-mass spectrometry (GC-MS) and Fourier transform infrared spectroscopy (FTIR) identified key active compounds, with (Z)-3- phenylacryldehyde as the major component (51.24%). Next, nano formulations of CBE-CS were developed, and their physicochemical properties were characterized, including particle size, zeta potential, encapsulation efficiency (33.9%), and loading capacity (48.78%). Antibacterial assessments demonstrated that the nano formulations effectively inhibited Burkholderia. glumae. Finally, greenhouse trials on rice seedlings confirmed the efficacy of these nano formulations in controlling BPB disease, showing significant bacterial suppression and improved plant health. These findings suggest that CBE-CS nanoparticles offer a promising, eco-friendly alternative for managing bacterial blight in rice, providing both effective antibacterial activity and enhanced plant protection.